Pengaruh Pelayanan Petugas Ruang Tunggu PT Angkasa Pura I Terhadap Kepuasan Pengguna Jasa di Bandar Udara Internasional Yogyakarta - Zakiah; Eny Sri Haryati (Jurnal Kajian dan Penelitian Umum, 2023)
Yogyakarta International Airport (YIA) is an international airport located in Temon district, Kulon Progo Regency, Special Region of Yogyakarta province. As an aviation service provider company, PT Angkasa Pura I needs to pay attention to the facilities and services in the passenger departure lounge. This research aims to discover the effect of the service of waiting room staff and how much influence it has on passenger satisfaction at Yogyakarta International Airport. This research uses quantitative methods. The data was collected through distributing questionnaires to 100 respondents using the waiting room area of domestic flights on November 1 to December 31, 2022. Data analysis was done by using simple linear regression with the service of the waiting room staff as the independent variable and passanger satisfaction as the dependent variable. The results show that the service of waiting room staff has a significant influence on passanger satisfaction, with a significance value of T = 16.293 > 1.661 with a significance value of 0.05. The service of waiting room staff as the independent variable influences passenger satisfaction by 73%. Meanwhile, the other 27% is influenced by other variables outside of this research. It can be concluded that Ho is rejected and Ha is accepted, which means that there is a significant influence of waiting room staff service on passanger satisfaction at Yogyakarta International Airport.